2022
DOI: 10.3390/brainsci12030382
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine as a Novel Psychopharmacotherapy for Eating Disorders: Evidence and Future Directions

Abstract: Eating disorders (EDs) are serious, life-threatening psychiatric conditions associated with physical and psychosocial impairment, as well as high morbidity and mortality. Given the chronic refractory nature of EDs and the paucity of evidence-based treatments, there is a pressing need to identify novel approaches for this population. The noncompetitive N-methyl-D-aspartate receptor (NMDAr) antagonist, ketamine, has recently been approved for treatment-resistant depression, exerting rapid and robust antidepressa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 166 publications
(184 reference statements)
0
13
0
1
Order By: Relevance
“…Therapeutic use of ketamine, a dissociative anesthetic the effects of which are mainly mediated by its NMDA receptor antagonism, can be also considered within the amino acidergic (glutamatergic) strategy [68] . Due to its rapid clinical effect in depression [69] , ketamine is extensively studied for other psychiatric indications, including EDs [70] . Preliminary clinical data on the efficacy and safety of ketamine in EDs suggest its therapeutic potential, but this should be confirmed in RCTs [70] .…”
Section: Resultsmentioning
confidence: 99%
“…Therapeutic use of ketamine, a dissociative anesthetic the effects of which are mainly mediated by its NMDA receptor antagonism, can be also considered within the amino acidergic (glutamatergic) strategy [68] . Due to its rapid clinical effect in depression [69] , ketamine is extensively studied for other psychiatric indications, including EDs [70] . Preliminary clinical data on the efficacy and safety of ketamine in EDs suggest its therapeutic potential, but this should be confirmed in RCTs [70] .…”
Section: Resultsmentioning
confidence: 99%
“…Primarily, we saw the low doses (1 mM) of ketamine, escitalopram, and fluoxetine increased both feeding and locomotion (Figure 4 and 5). Although the effects of ketamine on feeding had not been characterized in Drosophila , several new clinical studies have shown that microdosing ketamine increases appetite and has positive effects for patients with co-morbid eating disorders and depression (Ragnhildstveit et al, 2022; Robison et al, 2022; Schwartz et al, 2021). Similar to our Drosophila studies, low doses of ketamine also cause hyperlocomotion in mammals (Can et al, 2016; Irifune et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Insbesondere im Bereich der Depressionsbehandlung liegen zahlreiche Studien zur Wirksamkeit von Ketamin vor, darüber hinaus auch bei Zwangsstörungen, Autismus, Angststörungen und Abhängigkeitserkrankungen [20]. Für die Behandlung von Patient*innen mit AN liegen nur einzelne Fallserien mit kleinen Fallzahlen vor, welche Hinweise für eine Wirksamkeit auf einzelne Parameter geben [20,21]. Auf theoretischer Ebene geht man von einer positiven Beeinflussung der bei AN pathologisch veränderten Transmittersysteme (Serotonin, Dopamin) und neuropsychologischen Funktionen (Gedächtnis, Körperwahrnehmung) durch Ketamin aus [20].…”
Section: Anorexia Nervosaunclassified